Six-minute rowing test: a valid and reliable method for assessing power output in amateur male rowers - Huerta Ojeda,Álvaro; Riquelme Guerra,Miguel; Coronado Román,Walter; Yeomans-Cabrera,María-Mercedes; Fuentes-Kloss,Rodrigo (PeerJ, 2022)
Background Standardized tests are currently available to assess power output in elite rowers. However, there are no valid and reliable tests to assess power output in amateur rowers. Objective This study aimed to determine the validity and reliability of a 6-min rowing ergometer test (6-minRT) as a predictor of power output (PO) in amateur male rowers. Methods Twelve male amateur rowers were part of the study. All participants were instructed to perform an incremental test (IT), a 6-minRT test, and a retest. The validity of the 6-minRT was determined by comparing maximum oxygen uptake (VO2max) and power output (PO) between the IT and 6-minRT. Reliability included the coefficient of variation (CV), intra-class correlation coefficient (ICC), and mean standard error between the 6-minRT test and retest. The significance level was p < 0.05. Results There was no significant difference in VO2max in both IT and 6-minRT (p = 0.18), while the mean power output (Pmean) generated in the 6-minRT equaled 91.96% of the maximal aerobic power (MAP) generated in the IT (p = 0.004). Reliability analysis for the 6-minRT showed a CV = 0.50% and ICC = 0.97 for distance, a CV = 1.85% and ICC = 0.96 for Pmean. Conclusion From a ventilatory and mechanical point of view, the 6-minRT is a maximally valid test for establishing MAP in amateur rowers. Also, the 6-minRT evidences a high degree of agreement between days. Therefore, the 6-minRT is a valid and reliable test for assessing PO in amateur male rowers.
Keywords: Rowing; Amateur rowers; Power output; Validity; Reliability